Novel mixed finite element models for nonlinear analysis of plates - Wooram Kim (Latin American Journal of Solids and Structures)
In this study, mixed finite element models of plate bending are developed to include other variables (e.g., the membrane forces and shear forces) in addition to the generalized displacements to investigate their effect on nonlinear response. Various finite element models are developed using the weighted-residual statements of suitable equations. The classical plate theory and the first-order shear deformation plate theory are used in this study and the von Karman nonlinear strains are accounted for. Each newly developed model is examined and compared with displacement finite element models to evaluate their performance. Numerical results show that the new mixed models developed herein show better accuracy than existing displacement based models.